'ABER DORT LEBEN, WO ANDERE SIND WIE ICH, DAS MÖCHTE ICH GERN.'1 RUSSIAN‐GERMAN MIGRATION, EXCLUSION AND IDENTITIES IN ELEONORA HUMMEL'S NOVELS. (April 2015) - van den Brande, Deborah
ABSTRACT: This article discusses the connections between Russian‐German migration processes and the characters' self‐perception in two novels by the Russian‐German author Eleonora Hummel: Die Fische von Berlin (2005) and Die Venus im Fenster (2009). Both novels combine discrimination experienced in the Soviet Union with integration problems in Germany from a Russian‐German perspective. Although there are certainly parallels between Russian‐German literature and other migration texts, the specificity of Russian‐German migration processes and of their negotiation of identities calls for a cautious socio‐historical reading. By means of a close reading including insights from intercultural theories and Russian‐German history, this article analyses how the characters define themselves according to different cultural contexts and how these novels relate to extra‐textual Russian‐German history. Key concepts are 'Heimat', migration, language, family, identity, prejudices, the tension between assimilation and exclusion and the contrast between optimistic expectations and disillusionment. Dieser Beitrag untersucht die Verbindungen zwischen russlanddeutschen Migrationsprozessen und der Selbstwahrnehmung der Figuren in zwei Romanen der russlanddeutschen Autorin Eleonora Hummel: Die Fische von Berlin (2005) und Die Venus im Fenster (2009). In beiden Romanen wird die in der Sowjetunion erlebte Diskriminierung mit Integrationsschwierigkeiten in Deutschland aus russlanddeutscher Perspektive kombiniert. Obwohl sicherlich Parallellen zwischen russlanddeutscher Literatur und anderen Migrationstexten festgestellt werden können, erfordert die Spezifität russlanddeutscher Migrationsprozesse und Identitätsverhandlungen eine genaue sozio‐historische Lektüre. Ausgehend von einem Close‐Reading, das auf Einsichten aus interkulturellen Theorien beruht und auch die russlanddeutsche Geschichte berücksichtigt, analysiert dieser Aufsatz, wie die Figuren sich wechselnden kulturellen Kontexten entsprechend definieren und in welcher Beziehung diese Romane zu der extra‐textuellen russlanddeutschen Geschichte stehen. Wichtige Begriffe sind Heimat, Migration, Sprache, Familie, Identität, Vorurteile, die Spannung zwischen Assimilation und Ausgrenzung und der Kontrast zwischen optimistischen Erwartungen und Desillusionierung.